A new miniature Melanesian Forest Frog (Ceratobatrachidae: Cornufer) from New Britain Island, constituting the first record of the subgenus Batrachylodes from outside of the Solomon Archipelago - Travers, Scott L.; Richards, Stephen J.; Broadhead, Taylor S.; Brown, Rafe M. (Zootaxa, 2018)
We describe a new species of Cornufer, subgenus Batrachylodes, from high-elevation forests of New Britain Island in the Bismarck Archipelago of Eastern Melanesia. The new species, Cornufer exedrus sp. nov., is a biogeographically disjunct member of the Batrachylodes clade, representing the first record of the subgenus from outside of the Solomon Archipelago. The new species is a small terrestrial form from dense, closed-canopy forests above 1500 meters elevation in the Nakanai Mountains of eastern New Britain. It differs from its closest relatives, the other members of the subgenus Batrachylodes, on the basis of its minute body size, degree of digital disc expansion, reduced subdigital tuberculation, color pattern, and other traits related to its small size. We also provide a description of the new species’ simple advertisement call. The diversity of ceratobatrachid frogs of the Bismarck Archipelago is most likely still underestimated despite several recent surveys. Our understanding of evolutionary trends and species boundaries in the subgenus Batrachylodes currently is hampered by lack of genetic samples and call recordings corresponding to voucher specimens of the endemic species of Bougainville Island.